2022
DOI: 10.1590/1807-1929/agriambi.v26n2p119-125
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gas exchange of soursop under salt stress and hydrogen peroxide application

Abstract: The cultivation of irrigated soursop in semiarid Northeastern Brazil highlights the need for information regarding its responses to the salinity of irrigation water and the use of techniques that allow its exploration, such as the use of hydrogen peroxide. Thus, the study aimed to evaluate the effect of soaking of seeds and foliar application of hydrogen peroxide on soursop plant growth and physiology under conditions of salt stress. The study was conducted in lysimeters in a greenhouse, and the treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Despite the negative effects of salts, irrigation with saline water can be made possible through the use of hydrogen peroxide (H 2 O 2 ) (Andrade et al, 2019). Seed pre-treatment or plant exposure to H 2 O 2 is an important mechanism to modulate cross-tolerance through action on various physiological processes, such as photosynthesis and stomatal regulation, and on different stress-responsive pathways, such as detoxification of reactive species of oxygen (ROS) (Veloso et al, 2022).…”
Section: Treatmentsmentioning
confidence: 99%
“…Despite the negative effects of salts, irrigation with saline water can be made possible through the use of hydrogen peroxide (H 2 O 2 ) (Andrade et al, 2019). Seed pre-treatment or plant exposure to H 2 O 2 is an important mechanism to modulate cross-tolerance through action on various physiological processes, such as photosynthesis and stomatal regulation, and on different stress-responsive pathways, such as detoxification of reactive species of oxygen (ROS) (Veloso et al, 2022).…”
Section: Treatmentsmentioning
confidence: 99%
“…The decrease in CEi occurred because the deleterious effect of salt stress was greater on photosynthesis compared to internal carbon concentration. As salt stress becomes more severe, dehydration of mesophyll cells inhibits photosynthesis, mesophyll metabolism is impaired and carboxylation efficiency is compromised (Veloso et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The salinity levels of the water were established based on a study conducted by [ 15 ], who observed that water up to 2.0 dS m −1 can be used to produce soursop seedlings with an acceptable average reduction (up to 10%) in growth. Concentrations of hydrogen peroxide were based on the results of an assay conducted by [ 9 ], who verified that the use of hydrogen peroxide at the concentration of 20 μM attenuated the harmful effects of irrigation water salinity on the initial growth and gas exchange of soursop cv. Morada Nova.…”
Section: Methodsmentioning
confidence: 99%
“…In soursop, salt stress induces loss of photosynthetic activity due to stomatal and non-stomatal limitations [ 8 , 9 ]. It compromises the quantum efficiency of photosystem II (PSII), demonstrating that PSII reaction centers have experienced photoinhibitory damage, which results in the formation of reactive oxygen species (ROS) [ 10 ] capable of inducing oxidative damage to proteins and other biological components [ 11 ].…”
Section: Introductionmentioning
confidence: 99%